(untitled) (Research, Society and Development, 2022)
This article aims to show how a cluster analysis can be carried out, through the technical hierarchy and the non-hierarchy in the rate of infected by Covid-19 of the Brazilian states through the numbers of infected states in order to identify a similarity between the states. through the numbers of infected, offering a counterpoint to the criterion used to analyze the number of infected in the states, based on the size of the population and comparing with their Human Development Index (HDI). public and free platforms called Coronavirus//Brasil and Atlas Brasil 2013 in relation to the 2010 HDI. For the cluster analysis, the Mahalanobins matrix was used with the hierarchical method, the simple link, complete, average, ward link and a non-hierarchical method using the K-means method were also applied, the coefficient of confenetic correlation to measure the degree of fit between the original similar matrices and the matrix resulting from the simplification provided by the clustering method. However, the method that best represents the data was found to be the complete linkage method. When grouping the states of both data, it took into account the similarity between the variables of the data and the correlation where it can be observed that the data are correlated.